Sus scrofa Linnaeus 1758 ... - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
311. Sus scrofa Linnaeus, 1758 Common name: Eurasian Wild Pig, Wild Boar Myanmar name: Distribution: Distributed in all continents except Antarctica, and on many oceanic islands. In Myanmar, widely distributed and recorded in most of the PAs and RF throughout the country. ... : Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on pages 185-186, DOI: 10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939 ...